Designing the Framework of Specialization in the Recruitment of Non-Teaching Staff in Iran's Ministry of Education - Yoonesi, Mehrnaz; Jafari, Sakineh (Iranian Journal of Educational Sociology, 2022)
Purpose: The present study aimed to design a framework for recruiting non-teaching educational staff in Iran’s Ministry of Education.Method: The present study pursues a qualitative approach. The statistical population of the research included experts and professors in the field of specialization and the senior managers of the General Department of Education of Semnan province in the academic year of 2023-2024, among which 15 were chosen as the samples using theoretical saturation sampling and targeted sampling. The research instruments were a semi-structured interview and a review of the existing documents on this subject. The collected data were validated using member checking. The data validity was evaluated and confirmed using the quality criterion (reliability). The research data analysis method was thematic analysis in three levels: basic themes, organizing themes and Global Themes.Findings: The data analysis led to the identification of 393 basic themes, 33 number-one organizing themes, and 13 number-2 organizing themes in the field of specialization in recruiting non-teaching educational staff in the Ministry of Education. These themes were categorized under 4 global themes including expertise management with two organizing themes (expertise management and performance management), resource management with four organizing themes (human, time, material, and information), change management with three organizing themes (change in organizational structure, change in competitive atmosphere, and change in attitude), and management of organizational development with four organizing themes (managerial capabilities, human resource planning, creation of specialization culture, and organizational interactions).Conclusion: The use of elite and expert employees in the nonteaching sector of the educational system, as a leading institution in providing extensive services to the general public, depends on the presence of a specialization pattern in the recruitment of non-teaching staff. Identification of specialization criteria in the non-teaching sector, which has been done in this research, helps with the formulation of an appropriate specialization model to employ skilled and specialist staff in this sector.